2011
DOI: 10.1158/1078-0432.ccr-11-0234
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibitors Potentiate the Activity of the BCR/ABL Kinase Inhibitor KW-2449 in Imatinib-Sensitive or -Resistant BCR/ABL+ Leukemia Cells In Vitro and In Vivo

Abstract: Purpose The purpose of this study was to determine whether HDAC inhibitors (HDACIs) such as vorinostat or entinostat (SNDX-275) could increase the lethality of the dual Bcr/Abl-aurora kinase inhibitor KW-2449 in various Bcr/Abl+ human leukemia cells, including those resistant to imatinib mesylate (IM). Experimental Design Bcr/Abl+ CML and ALL cells, including those resistant to IM (T315I, E255K) were exposed to KW-2449 in the presence or absence of vorinostat or SNDX-275, after which apoptosis and effects on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 38 publications
4
61
0
1
Order By: Relevance
“…Our data showed the synergistic eVects of concomitant treatment with ZM and TMZ on glioblastoma cell lines and primary cultures, as observed in proliferation assays. This agrees with the Wndings of previous studies in which the inhibition of Aurora kinases by ZM augmented the antiproliferative eVects of other chemotherapeutic agents in human cancer cell lines (Georgieva et al 2010;Nguyen et al 2011;Zhang and Zhang 2011). We also found that ZM sensitized glioblastoma cells to radiation and this eVect was enhanced when ZM was associated with TMZ.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data showed the synergistic eVects of concomitant treatment with ZM and TMZ on glioblastoma cell lines and primary cultures, as observed in proliferation assays. This agrees with the Wndings of previous studies in which the inhibition of Aurora kinases by ZM augmented the antiproliferative eVects of other chemotherapeutic agents in human cancer cell lines (Georgieva et al 2010;Nguyen et al 2011;Zhang and Zhang 2011). We also found that ZM sensitized glioblastoma cells to radiation and this eVect was enhanced when ZM was associated with TMZ.…”
Section: Discussionsupporting
confidence: 92%
“…al. 2009;Nguyen et al 2011;Niermann et al 2011;Santo et al 2011). Our data showed the synergistic eVects of concomitant treatment with ZM and TMZ on glioblastoma cell lines and primary cultures, as observed in proliferation assays.…”
Section: Discussionsupporting
confidence: 68%
“…A number of reports have suggested that the increases in ROS generation may stem from Bcr-Abl kinase inhibition and that ROS levels are increased downstream of Bcr-Abl (24,25). However, in the present study, NAC reversed the cell death and Bcr-Abl downregulation induced by combined treatment of SAHA and MG-132, which indicates that the increase in ROS is upstream of Bcr-Abl downregulation and mediates the synergistic effect of SAHA and MG-132 in CML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the detection of low levels of BCR/ABL transcripts in CML patients is used in disease control strategies, new observations have demonstrated that malignant cell persistence is not necessarily dependent on higher activity in BCR/ABL signaling pathways (Jilani et al, 2008;Corbin et al, 2011;Nguyen et al, 2011). The reverse transcription-PCR technique is extremely sensitive, and can detect primary transcripts even at low levels of expression.…”
Section: Discussionmentioning
confidence: 99%